Seguridad Internacional en los años ochenta - Ullman, Richard (Estudios Internacionales, 1980)
This study focuses predominantly on the problem of international security. To suggest that the 1980s will bring a certain easing of the main tensions that have complicated international relations in recent years, and that many disputes will be susceptible to negotiated solutions, is not to say that the next decade will be less violent. Restricting intervention movements may very well constitute one of the most pressing security problems during the 1980s. The purpose of this analysis is certainly not to propose a clear rule of non-intervention, but to begin to suggest some of the considerations that should be considered taken into account when proposing conditions for a world in which the impact of violence diminishes.